Alleviation of Psychological Distress and the Improvement of Quality of Life in Patients With Amyotrophic Lateral Sclerosis: Adaptation of a Short-Term Psychotherapeutic Intervention - Oberstadt, Moritz Caspar Franz; Esser, Peter; Classen, Joseph; Mehnert, Anja (Frontiers in Neurology, 2018)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that is inevitably fatal. To be diagnosed with a terminal illness such as ALS deeply affects one’s personal existence and goes along with significant changes regarding the physical, emotional and social domains of the patients´ life. ALS patients have to face a rapidly debilitating physical decline which restrains mobility and impairs all activities of daily living. This progressive loss of autonomy may lead to a sense of hopelessness and loss of quality of life, which in turn may even result in thoughts about physician-assisted suicide. Here, we would like to propose a psychotherapeutic manualized, individual, semi-structured intervention to relieve distress and promote psychological well-being in ALS patients. This short-term intervention was originally developed for advanced cancer patients. “Managing Cancer and Living Meaningfully (CALM)” focuses on the four dimensions (i) Symptom management and communication with health care providers, (ii) Changes in self and relations with close others, (iii) Spirituality, sense of meaning and purpose and (iv) Thinking of the future, hope and mortality. We suggest to supplement the concept by two additional dimensions which take into account specific issues of ALS patients: (v) Communication skills and (vi) Emotional expression and control. This therapeutic concept named “ManagIng Burden in ALS and Living Meaningfully (mi-BALM)” may be a further treatment option to help improving quality of life of ALS patients.